Impact of age and treatment institution type on outcomes of patients treated for chronic lymphocytic leukemia in British Columbia, Canada. (April 2021) - Huang, Steven J.; Gerrie, Alina S.; Young, Sean; Tucker, Tracy; Bruyère, Hélène; Hrynchak, Monica; Galbraith, Paul; Al Tourah, Abdulwahab J.; Dueck, Gregory; Noble, Michael C.; Ramadan, Khaled M.; Tsang, Peter; et al.
Highlights: Patients treated at ≥70 years had shorter OS and CLL survival than younger patients. Old age at CLL therapy predicts shorter OS adjusting for del17p, Rai stage, chemoimmunotherapy. No difference in OS between patients treated at academic or community-based centre. Abstract: Older age has been shown to adversely impact overall survival (OS) in chronic lymphocytic leukemia (CLL) however, prior population-based studies did not analyze the impact of cytogenetic abnormalities or were prior to the availability of ibrutinib. Objectives: i) We sought to compare outcomes of patients based on their age at treatment to examine if older age has an impact on OS in patients who were treated during the period when fludarabine-rituximab was the standard upfront therapy and when ibrutinib was first introduced and ii) compare outcomes based on whether the patient received primary treatment at an academic or community-based centre. Methods: The BC Provincial CLL Database, a population-based databasewas used to include patients who have received treatment in British Columbia (BC), Canada between 2004 and 2016. Results: A total of 1122 patients were included (<70 years at treatment, n = 589) with median age at diagnosis 66 years. Younger patients had higher Rai stage (55% vs. 44% stage I-II, p < 0.001), higher lymphocyte count at diagnosis (13 × 10 9 /L vs. 10 × 10 9 /L, p = 0.004), greater proportion with B-symptoms at diagnosis (15% vs 10%, p = 0.004), shorter time from diagnosis to treatment (13.9 months vs. 21.4 months, p = 0.001), higher proportion treated at an academic centre (79% vs. 69%, p < 0.001) and more were treated with fludarabine-rituximab or FCR (69% vs. 42%, p < 0.001) compared to older patients. Older patients had both a significantly ( p < 0.001) shorter OS from treatment start (4.7 years) and disease specific survival (8.1 years) than younger patients (median OS and DSS not reached). Of interest, there was no difference in OS between patients treated at an academic centre or community centre ( p = 0.087). First-line treatment with chemoimmunotherapy improved OS (HR 0.465, 95% CI: 0.381–.567). Conclusions: Older age but not treatment-institution type adversely impacts overall survival and CLL survival in treated patients in BC.